1998
DOI: 10.1016/s0735-1097(97)00482-8
|View full text |Cite
|
Sign up to set email alerts
|

Marked Elevation of Brain Natriuretic Peptide Levels in Pericardial Fluid Is Closely Associated With Left Ventricular Dysfunction

Abstract: BNP levels in pericardial fluid served as more sensitive and accurate indicators of left ventricular dysfunction than did BNP levels in plasma. Thus, BNP may be secreted from the heart into the pericardial space in response to left ventricular dysfunction, and it may have a pathophysiologic role in heart failure as an autocrine/paracrine factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 20 publications
2
41
2
Order By: Relevance
“…9 The suppression of procollagen by natriuretic peptides was previously reported. 10,11 Type I collagen and the carboxy-terminal propeptide of procollagen type I, a marker of collagen type I synthesis, are the major components of many extracellular matrices, and its accumulation characterizes most fibrotic processes.…”
Section: What Are the Pathophysiologic Roles Of Atrial Natriuretic Pementioning
confidence: 78%
“…9 The suppression of procollagen by natriuretic peptides was previously reported. 10,11 Type I collagen and the carboxy-terminal propeptide of procollagen type I, a marker of collagen type I synthesis, are the major components of many extracellular matrices, and its accumulation characterizes most fibrotic processes.…”
Section: What Are the Pathophysiologic Roles Of Atrial Natriuretic Pementioning
confidence: 78%
“…BNP is mainly derived from the left ventricular wall, and is increased in patients with left and/or right ventricular dysfunction [5-7, 27, 28]. These peptides are also secreted in the pericardial fluid [8,9]. A previous clinical study showed that ANP and BNP levels in the pericardial fluid were correlated with and higher than the respective blood levels, showing more marked increases due to cardiac failure [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, objective assessment of the severity is very difficult. In clinical practice, atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP), which are vasoactive hormones secreted by the heart, are routinely used for the diagnosis, management, and prognosis of heart diseases with cardiac insufficiency, and their pericardial levels are also useful for this purpose [4][5][6][7][8][9][10][11][12][13][14][15]. Although a number of reports have suggested that postmortem biochemistry is one of the most productive ancillary procedures available to forensic pathologists [16][17][18][19], there appears to be no published data on the natriuretic peptides in postmortem investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Increased cardiac pressure or volume as well as neurohumoral factors can trigger the synthesis and release of peptides derived from proANP and proBNP. Circulating concentrations of ANP and NT-proANP primarily reflect increased preload, whereas BNP and NTproBNP concentrations primarily reflect increased heart afterload [47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Anp Bnp and N-terminal Propeptidesmentioning
confidence: 99%